Examining The Mediating Role Of Patient Satisfaction In The Relationship Between Service Quality And Loyalty In Faith-Based Private Hospitals - Ronny H. Walean; Leonard Stiefen Mumek; Deske W. Mandagi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Public health services play a crucial role in fulfilling the basic needs of society, particularly in ensuring equitable access to quality healthcare. This study aims to analyze the impact of service quality on patient satisfaction and loyalty at Manado Advent Hospital, a faith-based private hospital in North Sulawesi, Indonesia. Using a quantitative research design, this study employed the SERVQUAL framework, which encompasses five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Data were collected from a sample of 208 inpatients through structured questionnaires distributed in September to October 2024. Structural Equation Modeling (SEM) was conducted using SmartPLS to test 11 proposed hypotheses. The findings indicate that four service quality dimensions, tangibility, reliability, responsiveness, and empathy, positively and significantly influence patient satisfaction, which in turn significantly affects patient loyalty. These results underscore the mediating role of patient satisfaction in enhancing loyalty, emphasizing the need for management to focus on specific quality dimensions to improve overall service performance. The study offers theoretical and practical implications for service quality improvement strategies in faith-based healthcare institutions.